Serek ha-Yaḥad (1QS) in dialogue with mimetic theory: Scapegoat mechanisms unveiled - Skarström Hinojosa, Kamilla (Studies on the texts of the desert of Judah, 2024)
"What holds a society together, what makes it dissolve, and how is a society in crisis restored? These are the questions explored in this study, which brings the Serek ha-Yahad (IQS) into dialogue with mimetic theory. It thus aims to shed light on the forms of life and thought in the yahad, as well as on their underlying reason and purpose. From the analysis emerges an image of a community that not only has a strong awareness of the mechanisms of violence, but also of its cure. Its hierarchical organization and strict regulations are motivated by a perceived dissolution of contemporary society. By subordinating personal desire to community discipline and by establishing a system of differentiation, the yahad seeks to provide a model of how a society ought to be functioning"--